Photophysical and Electrochemical Studies of Multinuclear Complexes of Iron(II) with Acetate and Extended Conjugated N-Donor Ligands - Norbani Abdullah; Suhana Mohd Said; Anita Marlina; Muhamad Faris Roslan; Afiq Azil; Abdul Rahman Nordin (The Scientific World Journal)
A dimeric iron(II) complex, trans-[Fe2(CH3COO)4(L1)2] (1), and a trinuclear iron(II) complex, [Fe3(CH3COO)4(H2O)4(L2)] (2), were studied as potential dye-sensitised solar cell materials. The structures of both complexes were deduced by a combination of instrumental analyses and molecular modelling. Variable-temperature magnetic susceptibility data suggested that 1 was made up of 56.8% high-spin (HS) and 43.2% low-spin (LS) Fe(II) atoms at 294 K and has a moderate antiferromagnetic interaction (J = −81.2 cm−1) between the two Fe(II) centres, while 2 was made up of 27.7% HS and 72.3% LS Fe(II) atoms at 300 K. The optical band gaps (Eo) for 1 were 1.9 eV (from absorption spectrum) and 2.2 eV (from fluorescence spectrum), electrochemical bandgap (Ee) was 0.83 eV, excited state lifetime (τ) was 0.67 ns, and formal redox potential (E′(FeIII/FeII)) was +0.63 V. The corresponding values for 2 were 3.5 eV (from absorption spectrum), 1.8 eV (from fluorescence spectrum), 0.69 eV, 2.8 ns, and +0.41 V.